Assessment of economic burden due to COVID-19 pandemic during institutional childbirth in Nepal: before-and-after design - Ashish KC; Rejina Gurung; Prajwal Paudel; Honey Malla; Avinash K Sunny; Mats Målqvist; Omkar Basnet; Pratiksha Bhattarai (BMJ Public Health)
Introduction The COVID-19 pandemic caused disruptions in global health and economic stability. In Nepal, before the pandemic, more than 50% of healthcare costs were out-of-pocket expenditure (OOPE). This study aimed to assess the OOPE for maternity care during before and during the COVID-19 pandemic in nine hospitals in Nepal.Method We conducted a before-and-after study between March 2019 and December 2020 with 13 months of prepandemic period and 9 months of pandemic period. OOPE was assessed using a semistructured interview with 53 864 women. Bivariate (unadjusted) and multivariate (adjusted) linear regression modelling was conducted to assess the change in OOPE in US dollar between the periods. Adjustment in linear regression model was done for population characteristics different between the periods.Result The OOPE for childbirth increased by 28.1% during pandemic, with an increase of OOPE from US$19.2 to S$23.9 (adjusted-β coefficient 5.4; 95% CI 4.5 to 5.7; p<0.0001). The OOPE of laboratory diagnosis increased by 15.3% for spontaneous birth during the pandemic (adjusted-β coefficient, 1.6; 95% CI 1.4 to 1.8; p<0.0001). OOPE increased by 29.8%, 40.0% and 10.3% for spontaneous vaginal birth, instrumental birth and caesarean section, respectively. The OOPE among the poorest family increased by 12.9%, and OOPE for richer family increased by 57.6% during the pandemic period.Conclusion OOPE for maternity care increased by more than 28% during the COVID-19 pandemic in Nepal. OOPE increased in all wealth quintile with marked rise in richer wealth quintile group. Mitigation efforts to secure affordable maternal healthcare services are required during pandemic.